Illocutionary Acts and Politeness Strategies Implied In Puppet Show Characters â€œBambang Wisanggeniâ€ - Brinda, Sonya; Junining, Esti; Chojimah, Nurul (Jurnal Budaya, 2020)
One of the cultural heritages in Indonesia which tell about the social life or human nature is puppet show or â€œWayangâ€. This research investigates Illocutionary Acts and Politeness Strategies Implied in one of the Puppet Show Characters â€œBambang Wisanggeniâ€. This study aims to reveal the types of illocutionary acts and politeness strategies. The method used in this research is descriptive qualitative method. The data were collected from the transcript of Bambang Wisanggeniâ€™s story. The study revealed that the types of illocutionary acts found in Bambang Wisanggeniâ€™s story were directive, assertive, commissive, and expressive. However, declarative act was not evident in this study since the character of Bambang Wisanggeni did not have power to do immediate changes with his utterances. Meanwhile, the types of politeness strategies found in Bambang Wisanggeniâ€™s utterances were bald on record strategy, positive politeness, and negative politeness. Off record strategies was not observed in this study because the whole utterance stated by the Bambang Wisanggeni was stated directly and clearly.